Incidence of Post-spinal Hypotension during Cesarean Section in Paropakar Maternity and Women’s Hospital - Shrestha, Sangeeta; Gurung, Tara; Pradhan, Ritu; Shrestha, Amir Babu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Spinal anesthesia is the choice of anesthesia in parturient for cesarean section. This procedure is frequently associated with hypotension and the incidence varies from 70% to 80%. Maternal hypotension causes very unpleasant sign and symptoms such as nausea, vomiting, dyspnoea and sense of impending doom. Prolonged episodes of hypotension lead to organ ischemia, loss of consciousness, cardiovascular collapse and uteroplacental hypoperfusion. The aim of this study is to find out the proper data of the incidence of hypotension in parturient undergoing cesarean section in our hospital as only the estimated data is present. Methods: We retrospectively reviewed the intraoperative anesthesia record form of all the patients who underwent cesarean section under spinal anesthesia from the hospital record section from 13th April 2016 to 12th April 2017. The detailed parameters of patient’s demographic data were collected and recorded. Results: A total of 3814 parturients were included in this study. The mean age was 25.76 ± 4.74 years and mean gestational age was 39.23 ± 1.54 weeks. Post spinal hypotension was seen in 947 patients out of 3814. Thus the incidence of hypotension was 24.8%. Conclusions: The incidence of maternal hypotension is very high if prophylactic measures are not taken. The fluid preloading or coloading, left lateral uterine displacement and prophylactic vasopressors have shown to be effective in preventing postspinal hypotension.